40 años después… ¿Dónde quedó la moral?: la importancia de recuperar el estudio del derecho civil desde la perspectiva de la filosofía moral - Escobar Rozas, Freddy (2024)
In the context of the fortieth anniversary of the Peruvian Civil Code, Dr. Freddy Escobar, one of the few national civil lawyers who has ventured into the study of Civil Law from the perspective of moral philosophy, offers us some important insights into the subject, its historical implications and its practical application.Furthermore, he assesses the work carried out by the lawmaker of the 1984 Civil Code from the aforementioned perspective. In our opinion, this is a necessary exercise, as in our environment this type of balance is usually formal or, in the best of cases, dogmatic. However, Professor Escobar’s contribution in this area is not limited to the narrow confines of this interview but is also (and above all) to be found in his written work. Some of the titles that we enthusiastically recommend are the following: Contratos: Fundamentos económicos, morales y legales (2020); Reglas insensatas: Las inconsistencias conceptuales, estratégicas y políticas del Código Civil (2021); and Justicia correctiva vs. justicia funcional: Aristóteles, Bentham y el sistema de remedios legales (2023).This Editorial Board hopes that the following lines will be as helpful to the reader as they were to us. Institutions, especially civil ones, cannot be evaluated based on law itself, but must pass through the yardstick of morality and economic efficiency.